Intensity and Prevalence of Psychological Distress in Cancer Inpatients: Cross-Sectional Study Using New Case-Finding Criteria for the Hospital Anxiety and Depression Scale - Muzzatti, Barbara; Agostinelli, Giulia; Bomben, Francesca; Busato, Sara; Flaiban, Cristiana; Gipponi, Katiuscia Maria; Mariutti, Giulia; Mella, Sara; Piccinin, Marika; Annunziata, Maria Antonietta (Frontiers in Psychology, 2022)
Psychological distress includes all negative subjective experiences elicited by a disease and its treatments. Since psychological distress in oncology is associated with negative outcomes, its detection and description are helpful for designing tailored supportive interventions. This study used the Hospital Anxiety and Depression Scale (HADS) to assess the intensity and prevalence of psychological distress (i.e. anxiety and depression) in cancer inpatients and examined the relationships between these variables and sociodemographic and clinical factors. An existing dataset of HADS results, from 2021 consecutive adult cancer inpatients at a single hospital, was analysed. Only those questionnaires with complete responses were used. The intensity of anxiety and depression was determined from HADS sub-scores. The prevalence of anxiety and depression was calculated using, as case-finding criteria, cut-offs of ≥10 and ≥8, respectively. The mean HADS scores describing intensity were 7.3 for anxiety (n=1990) and 5.8 (n=1970) for depression. The prevalence rates for anxiety and depression were 26.6% and 28.6%, respectively. Among the 1916 patients who completed both subscales, 17.2% had both anxiety and depression, 21.0% had either anxiety or depression, and 61.7% had neither. Gender, age, occupational status and cancer diagnosis were associated with anxiety intensity or prevalence, while age, occupational status and cancer diagnosis were associated with depression intensity or prevalence. Anxiety intensity was affected by the interaction effect between gender and diagnosis. Our study showed anxiety and depression being distinct entities, with more intense anxiety overall. From a research perspective, it reaffirms the usefulness for assessing both intensity and prevalence concurrently to gain a more detailed description of anxiety and depression.